The statesman in Plutarch's Greek and Roman lives - Blois, Lukas de. (Mnemosyne, Supplements, 2004)
This volume presents the second half of the proceedings of the Sixth International Conference of the International Plutarch Society (2002). The selected papers are divided by theme in sections concentrating on statesmen and statesmanship in Plutarch's Greek and Roman Lives . The volume bears witness to the ongoing, wide-ranging interest in Plutarch's biographies.